Immunogenic cell death of dendritic cells following modified vaccinia virus Ankara infection enhances CD8+ T cell proliferation. Issue 12 (10th October 2018) - Tappe, Kim A.; Budida, Ramachandramouli; Stankov, Metodi V.; Frenz, Theresa; R. Shah, Harshit; Volz, Asisa; Sutter, Gerd; Kalinke, Ulrich; Behrens, Georg M. N.
Abstract: "Immunogenic cell death" (ICD) is associated with the emission of so‐called damage‐associated molecular patterns (DAMPs) which trigger the immune response against dead‐cell associated antigens. The secretion of the DAMP, adenosine triphosphate (ATP) has been shown to be autophagy‐dependent. Here, we demonstrate that Modified Vaccinia virus Ankara (MVA), a highly attenuated strain of vaccinia virus, induces both cell death and autophagy in murine bone marrow‐derived dendritic cells (BMDCs), which in turn confer the (cross‐)priming of OVA‐specific cytotoxic T cells (OT‐I cells). Additionally, we show that MVA infection leads to increased extracellular ATP (eATP) as well as intracellular ATP (iATP) levels, with the latter being influenced by the autophagy. Furthermore, we show that the increased eATP supports the proliferation of OT‐I cells and inhibition of the P2RX7 receptors results in an abrogation of the proliferation. These data reveal novel mechanisms on how MVA enhances adaptive immunity in vaccine strategies. Abstract : Infection with modified vaccinia virus Ankara (MVA) leads to the autophagy‐dependent release of ATP and apoptosis of the infected dendritic cells (DCs). The apoptotic bodies from the infected DCs are captured by the bystander DCs and cross‐presented to the CD8 + T lymphocytes.